2015
DOI: 10.1002/pat.3723
|View full text |Cite
|
Sign up to set email alerts
|

Growth feature of PTFE coatings on rubber substrate by low-energy electron beam dispersion

Abstract: Polytetrafluoroethylene (PTFE) coatings were prepared on Si and acrylonitrile-butadiene rubber substrates by lowenergy electron beam dispersion. The effects of substrate nature, distance of target to substrate (d ts ) and coatings thickness on the surface morphology, structure, and tribological properties of the coatings were investigated. The results showed that substrate nature affects the shape and size distribution of surface conglomerations of PTFE coatings due to the interaction process of active dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The relative intensity ratios of characteristic peak of Cu–PTFE coatings are summarized in Table . The intensities of the bands at 516 and 638 cm −1 of Cu–PTFE composite coating are lower than for PTFE coating, indicating that Cu doping weakens the crystallinity and ordering degree of PTFE coatings. This may be because of the interaction of Cu with PTFE in the process of electron beam dispersion, that is, Cu particles as the nucleation centers enter into the polymer phase and change the molecular structure of PTFE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative intensity ratios of characteristic peak of Cu–PTFE coatings are summarized in Table . The intensities of the bands at 516 and 638 cm −1 of Cu–PTFE composite coating are lower than for PTFE coating, indicating that Cu doping weakens the crystallinity and ordering degree of PTFE coatings. This may be because of the interaction of Cu with PTFE in the process of electron beam dispersion, that is, Cu particles as the nucleation centers enter into the polymer phase and change the molecular structure of PTFE.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the SEM images of surface and cross section of PU–PTFE composite coatings without and with glow discharge treatment. Different from PTFE coating, the growth process of PU single coatings includes the melting of PU target and the agglomeration of droplet phase, which is described in detail in the previous work . The large size of protuberance structure on substrate surface and the droplets size of smaller than 0.1 µm are observed from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be from Fig. a observed that PE‐PTFE composite coating is considerably different from the morphological feature of PE and PTFE single coatings that reported in the previous work . There is no distinct columnar structure like the PTFE coating from cross‐sections morphology, whereas forms spherical aggregations.…”
Section: Resultsmentioning
confidence: 64%
“…Insufficient knowledge of polymeric materials tribology results from the complex multiphase structures of polymers, which make evaluation of their tribological behavior relatively difficult . With respect to the coating materials, fluoroligomeric coatings have been used to modify rubber products changing the surface morphology, and moreover improving the hydrophobic and tribological properties, e.g., polytetrafluoroethylene (PTFE) . The enhancement of protective properties is due not only to the barrier effect, but also to the obstruction effect of structural aggregations of the coatings on the process of liquid extension on the surface of modified rubber.…”
Section: Introductionmentioning
confidence: 99%